Un établissement du début du premier âge du Fer en Eure-et-Loir : Sours, Les Ouches - Frédéric Dupont; Bruno Lecomte; Jérémie Liagre; Julie Rivière; Jonathan Simon (Revue Archéologique du Centre de la France)
The excavation of the site of Ouches at Sours (28) has enabled the updating of an important settlement from the early Neolithic and the discovery, in the northern part of the site, of several structures datable to the beginning of the Iron Age (Hallstatt C). They correspond to domestic structures (a building and some ditches) and a “worship” entity: a double enclosure in a “U” shape.The dwelling and its annexes are represented by a quadrangular building on posts and a large ditch which is rich in furnishings (ceramic, bone and worked flint). This structure may be associated to the working of a “Polynesian” type kiln and serve as a reject pit. The double enclosure, open towards the north) is situated to the north-east of the site.Even though three entire ceramic vessels have been found in the outer ditch, the majority of the ceramic furnishings (177 out of 192) have come from the large ditch, principally cups, bowls which are sometimes inscribed, small goblets with a globular middle typical of Hallstatt C or vessels used for storing. They regularly have finger made cords.This small dwelling from the beginning of the Iron Age has provided a good sample of ceramics in use in Eure-et-Loir in this period as well as some archaeozoological remains and lithics in interesting quantities. These discoveries provided new information on the cultural affinities to the transition between the Bronze and Iron ages, a period which is little researched in the north of the Centre region.